(untitled) (UNIZIK Journal of Marketing, 2024)
This paper proposes a conceptual framework for sustainable tax compliance, integrating behavioral, institutional, and environmental determinants. Using recent literature, this framework identifies key factors influencing compliance, including trust in tax authorities, perceived fairness, the impact of digital technologies, and the role of environmental taxes. The paper emphasizes the need for robust policy implications, providing recommendations for policymakers on enhancing sustainable tax compliance through evidence-based strategies. Visual representations, including a conceptual framework diagram and graphs, illustrate the interactions among these determinants. The framework aims to support policymakers in designing interventions that foster voluntary compliance while aligning with broader environmental and economic goals.